Organization measures in the Enhanced Baking Tray Task - Argiuolo, Antonietta; Somma, Federica; Bartolomeo, Paolo; Gigliotta, Onofrio; Ponticorvo, Michela (Frontiers in Psychology, 2022)
The ecological assessment and the analysis of spatial organization behaviours, like the organization of objects in an empty space, in clinical and neurotypical conditions, is crucial. The Enhanced-Baking Tray Task (E-BTT) is as simple as that – placing objects inside a frame as evenly as possible, as they were “cookies” to be baked in the oven. The E-BTT is the enhanced version of an ecological task for neglect assessment, the Baking Tray Task, and has the advantage to register the coordinates of each object and their temporal order, meaning that it is easy to reconstruct the sequence of their placement. This sequence could be further analyzed, and, in this paper, we aim to do that with a series of indexes. Moreover, since they investigate the visual search organization of the sequence itself, their validity will be tested with a convergent measure of subjective organization. Therefore, we asked 100 observers (76 women) to evaluate the subjective organization of each of the 97 E-BTT plots, on a scale that ranged from 0=not at all to 100=well organized. Results showed a significant association between subjective organization ratings and Intersection rate (r=-0.77, p<0.05), correlations of each coordinates series and their order (respectively R_X: r=0.26, p<0.05 and R_Y: r= -0.36, p<0.05), total time of performance (r=-0.30 p<0.05) and distance to both optimal sequences (r=-0.36, p<0.05 and r=-0.33, p<0.05). Then the above-mentioned indexes can be considered measures of the overall organization also in the E-BTT.